2012
DOI: 10.1103/physrevd.86.045011
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance properties of baryons in the Sakai–Sugimoto model

Abstract: Abstract:We reconsider the realization of baryons in the Sakai-Sugimoto model. In this theory, which is the gravity dual of a QCD-like theory, baryons appear as soliton solutions. These solitons were approximated as flat-space instantons in previous studies. However, with this approximation, it has been shown that one does not reproduce some modelindependent predictions for the behavior of baryon electromagnetic form factors which are connected with long-range pion physics. This made it appear that the long-ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…Here we explicitly prove this statement, generalizing the asymptotic instanton solutions found in [21,25] to an arbitrary background. A few ambiguities in the solutions are clarified during our analysis.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Here we explicitly prove this statement, generalizing the asymptotic instanton solutions found in [21,25] to an arbitrary background. A few ambiguities in the solutions are clarified during our analysis.…”
Section: Introductionsupporting
confidence: 65%
“…[25] it was shown that, solving the full set of equations of motion, the correct power behavior can be recovered in this model. In the following sections we give a modelindependent derivation for the form factors, showing that the linear approximation used in the meson sector is not suitable for describing baryons, and that the resulting VMD picture for nucleons is doubtful.…”
Section: B Linear Approximationmentioning
confidence: 96%
See 1 more Smart Citation
“…Once the correct algebraic decay is recognized the puzzle evaporates, as it was simply a consequence of applying a linear result beyond its region of validity. The algebraic decay of the holographic Skyrmion fields was first discovered by Cherman and Ishii 36 , who performed a large r expansion to obtain the asymptotic fields. However, they were only able to implement their approach by introducing a UV cutoff, with an associated singularity in the limit as this cutoff is removed: prompting them to speculate on possible resolutions that included holographic renormalization and boundary counterterms.…”
Section: The Holographic Skyrmion In the Sakai-sugimoto Modelmentioning
confidence: 99%
“…5 In contrast to previous treatments of the model, we directly solve for the long-distance behavior of the holographic baryon. We find that the structure of this long-distance solution is such that Eq.…”
Section: Introductionmentioning
confidence: 99%